Wisdom and management: a conceptual study on wisdom management - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Essentially, management and philosophy contribute each other in ever aspects and this is creating a managerial philosophy since managers face uncertainties during their decision making process in every day. Managers could not realize their creativity without any philosophical thought and questioning (Moseley, 2010). Philosophy is a love of wisdom, however, wisdom could be determined according to what individuals think and what they see. Unwise people, close their minds, emotions and senses, they prefer not to observe, feel and think (McKenna and David, 2005). Wisdom implies combination of knowledge and thoughts around predetermined principles. Wisdom includes both rational (scientific) intellectual practices and mental processes. In that case, our vision and related strategies explain meaning of our lives and how we could spend such life. Human beings are trying to make sense the world around them with limited knowledge, struggle to create a synergy between the mind and character and to balance both sides well being and truths (McKenna and David, 2005). Todays managers are obliged to make strategic decisions in every day and during this process they analyze their immediate environments and look at their personal backgrounds. Some of them reap the rewards of positive returns, on the other hand, the others stand to failures (Malan and Kriger, 1998). Regarding to this difference, we will be aware of some latent concept wisdom, that has not been analyzed in the management and organization literature, especially in leadership studies until now. Even this concept has not been discussed in the psychology literature until 1980s, but both disciplines has just begun to analyze it recently (McKenna, Rooney and Kenworthy, 2013). Although many researches in this field are interested in developing a valid definition but there is no agreement on the precise definition of wisdom (Schmit, Muldoon and Pounders, 2012). However, definition efforts made for twenty years could be considered constructive in clarifying old but newly emerged concept. Besides, the point of multidimensional construct of wisdom is supported by many researchers.(Webster, 2003). Wisdom is referred to the top of an inner voice about human nature and the tools leading to the attainment of life objectives (Baltes and Staudinger, 2000). In other words, wisdom represents an idea about complicated and uncertain situations such as cognitive functioning, intellectual development, life planning and management. It denotes a process rather than a specific situation(Ardelt, 2003; 2004). Wisdom dimensions on which there is an agreement includes practical, reflective, openness to experience, interactional tendency, tolerance for ambiguities, ethical sensitiveness and having an experience (Munro, 2012; Schmit vd. 2012; Webster, 2003). Thus, this study aims to gain holistic perspective with explicit and implicit assumptions regarding wisdom by using different definitions made before. Also, this study aims to suggest clues on how to develop wisdom and how to apply it into the management field, i.e managerial wisdom. This descriptive research tries to light the way of new applications of wisdom rather than measuring managerial wisdom levels of individuals via empirical research. Main research question of this study is whether it is sufficient to have a technical knowledge in any field in order to be successful. (C) 2014 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).
Keywords: Managerial Philosophy; Wisdom Management; Wise Individual; KNOWLEDGE